Influence of Classroom Teacher Practices on the Teaching and Learning Effectiveness in Secondary Schools in Tanzania: A Case of Selected Schools in Kilimanjaro By (International Journal of Scientific Research and Management (IJSRM), 2021)
The study focused on investigating the influence of classroom teacher practices on teaching and learning effectiveness in secondary schools. The study used a number of different psychological perspectives relating to the teaching and learning process in school classrooms such as behaviourism and constructivism ideas to establish the basis for effective teacher practices and characteristics in relations to teaching and learning process. A cross section survey and naturalistic design method was used to investigate the influences of teacher practices in selected secondary schools. A simple random sampling and automatic inclusion was used, and the selected sample was made up of 200 secondary school teachers, 10 of whom were heads of schools. The data collection process included interviews, classroom observation and questionnaire instruments. The findings indicated that the teaching and learning process is greatly influenced by teacher practices and characteristics. Teachers demonstrated little knowledge of teaching techniques and skills to improve teaching effectiveness and pupil learning. The study concludes that teaching and learning processes can be improved by providing teacher support and improving the quality of teacher education through professional development practices to update teacher skills. The study recommends that efforts should be made to improve instructional processes in schools in order to achieve the intended educational goals through different strategies such as seminars, workshops, improved In-service teacher Education at school, District and National levels.